Hubungan Pengetahuan Ibu Dengan Kesiapan Menghadapi Menopouse Di Desa Waihatu Kecamatan Kairatu Kabupaten Seram Bagian Barat - Syahfitrah Umamity (USADA NUSANTARA : Jurnal Kesehatan Tradisional, 2024)
Background: Menopause comes from the Greek word meaning "month", which linguistically is more accurately called "menocease" which means the cessation of menstrual periods. Menopause is known as the permanent cessation of menstruation which occurs following the loss of ovarian activity and is also often interpreted as the end of a woman's reproductive function for 2 full months. Before the menopause phase occurs, it is usually preceded by the premenopausal phase, where in the premenopausal phase there is a transition from the fertile period to the period of absence of fertilization. Most women begin to experience pre-menopausal symptoms in their 40s and the peak is reached at the age of 50, namely the onset of menopause. Readiness is defined as a condition in which a mother prepares herself to face menopause, both physically, psychologically and spiritually. A woman who is approaching menopause should always think positively that this condition is something natural. The aim of this research is to determine the relationship between maternal knowledge and readiness to face menopause in Waihatu Village, Kairatu District, West Seram Regency, as well as identify mothers' knowledge and readiness to face menopause. This research design uses a quantitative type of research using correlation analytical methods with a cross sectional design. Based on the research results, it can be seen that the number of respondents was 124 mothers, consisting of 8 mothers (6.5%) who had good knowledge, while 54 mothers (43.5%) had sufficient knowledge and 62 mothers (50.0%) had poor knowledge. This research also produced respondents who were ready to face menopause in the not ready category as many as 89 mothers (71.8%) and the ready category as many as 35 mothers (28.2%).